Review: Roles of Prebiotics in Intestinal Ecosystem of Broilers - Teng, Po-Yun; Kim, Woo Kyun (Frontiers in Veterinary Science, 2018)
In recent years, prebiotics have been considered as potential alternatives to antibiotics. Mechanisms by which the prebiotics modulate the ecosystem of gut include alternation of intestinal microbiota, improvement of epithelium, and stimulation of immune system. It is suggested that the administration of prebiotics not only influences on these aspects but also regulates the interaction between the host and intestinal microbiota comprehensively. In this review, we will discuss how each prebiotic ameliorates the ecosystem by direct or indirect mechanisms. Emphasis will be placed on the effects of prebiotics, including mannans oligosaccharides, β-glucans, and fructans, on the interaction between the intestinal microbiota, gut integrity and the immunity of broilers. We will highlight how the prebiotics modulate microbial community and regulate production of cytokines and antibodies, improving gut health and overall broiler health. Understanding the cross-talk between prebiotics and the intestinal ecosystem might provide us novel insights and strategies for preventing pathogen invasion and improving health and productivity of broilers. However, further studies should be conducted to identify the appropriate dosages and better resources of prebiotics for refinement of administration, as well as elucidate the unknown mechanisms of action.